2016
DOI: 10.1111/1467-8551.12182
|View full text |Cite
|
Sign up to set email alerts
|

Reporting and Justifying the Number of Interview Participants in Organization and Workplace Research

Abstract: In this paper we examine established practice regarding the reporting, justification and number of interview participants chosen within organization and workplace studies. For such qualitative research there is a paucity of discussion across the social sciences, the topic receiving far less attention than its centrality warrants. We analysed 798 articles published in 2003 and 2013 in ten top and second tier academic journals, identifying 248 studies using at least one type of qualitative interview. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
271
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(313 citation statements)
references
References 48 publications
(107 reference statements)
15
271
0
Order By: Relevance
“…We predict that interviews from 16 learners will generate enough data for answering the research questions and perform the analyses because based on past qualitative interview research review, 16 interviews is within the range of an acceptable number of interviews [16]. However, if there is a need for further investigation of further phenomena or themes, we will endeavour to get more participants into being interviewed for the study.…”
Section: Sample Sizementioning
confidence: 99%
“…We predict that interviews from 16 learners will generate enough data for answering the research questions and perform the analyses because based on past qualitative interview research review, 16 interviews is within the range of an acceptable number of interviews [16]. However, if there is a need for further investigation of further phenomena or themes, we will endeavour to get more participants into being interviewed for the study.…”
Section: Sample Sizementioning
confidence: 99%
“…Likewise, given only recent corporate interest in D&I, it is not possible to assess the potential manager population from which we could gather data. Following Saunders and Townsend (2016), a sample of 20 (15 LGBT employees and five managers) is within acceptable boundaries for meaningful analysis, especially for difficult-to-access respondent population groups.…”
mentioning
confidence: 99%
“…Studies reveal a large variation in the number of interviews performed in different research contexts. Acknowledging exceptions, and dependent on study purpose a norm of around 15-60 participants was observed in a recent study (Saunders & Townsend 2016). Marshall (2013) drew on studies reporting participants in five information systems journals, it was inferred, that 'collective wisdom' suggested 15-20 participants for single case study research.…”
Section: Methodsologymentioning
confidence: 99%
“…In seeking out 'senior' practitioners I was looking for participants typically at manager level and above who had experience in developing value propositions from different levels and perspectives at the SMI to help provide rich perspectives of the phenomenon. The size of the sample was determined in relation to the purpose of the research and with a view to project timescales (Miles & Huberman 1994), and in line with the broad benchmark for participants identified in previous studies as outlined in 3.5 (Marshall 2013;Saunders & Townsend 2016). The expediency of not too large a sample to make depth analysis difficult whilst making data saturation attainable was also a consideration (Onwuegbuzie & Leech 2005 Data saturation can be deemed to have been reached when no further significant insights are emerging (Glaser & Strauss 1967).…”
Section: Research Samplementioning
confidence: 99%